2018
DOI: 10.3390/ma11061014
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Loess Using Nano-SiO2

Abstract: Improving the performance of loess is of significant importance for lowering its collapsibility and water sensitivity to construction requirements and for geohazard mitigation. The present paper studies the changes in mechanical, structural, and mineralogical properties of nano-SiO2-treated loess with different contents and curing days. The mechanical behavior was examined by unconfined compressive strength (UCS) of untreated and treated loess. To better understand the mechanisms of stabilization, particle siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…Geopolymer can be synthesized by mixing calcined kaolin and strongly alkaline solutions (such as NaOH or KOH) and then curing at a room temperature [10]. Several studies have examined the use of various geopolymers for loess soil stabilization, including fly ash, lime, and cement, etc., [11][12][13][14][15][16]. However, the use of the anhydrous calcined form of the clay mineral kaolinite (metakaolin) was given less attention in loess stabilization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Geopolymer can be synthesized by mixing calcined kaolin and strongly alkaline solutions (such as NaOH or KOH) and then curing at a room temperature [10]. Several studies have examined the use of various geopolymers for loess soil stabilization, including fly ash, lime, and cement, etc., [11][12][13][14][15][16]. However, the use of the anhydrous calcined form of the clay mineral kaolinite (metakaolin) was given less attention in loess stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…Loess is a widespread surface deposit in many parts of the world. There is a strong need for loess stabilization in construction requirements and geohazard mitigation due to its propensity to collapse and subsidence after loading and wetting [11,12]. Moreover, unpaved roads in loess are associated with strong erosion by wind and water, which leads to soil disintegration [7].…”
Section: Introductionmentioning
confidence: 99%
“…Shafiq [22] and Murthy et al [23] discussed the influence of nano-SiO 2 on the mechanical properties and durability of concrete. Kong et al [24] found that nano-SiO 2 could effectively improve the unconfined compressive strength of loess and improve pore structure. The above explorations have enriched the research on the improvement of the properties of soil stabilizers, but generally speaking, compared with the broad application prospects showed by soil stabilizers as materials for efficient utilization of soil and water resources, the current research status still needs to be deepened.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, fly ash, cement and lime are leading inorganic additives used in the soil stabilization. Due to their calcium-based structure, they frequently endure chemical reactions with the soil in the presence of water resulting in an overall improvement of the soil physicochemical properties 11 . Among these additives, fly ash owing to cost-effectiveness and abundance, dominantly attracts more consumers rather than lime in the construction industry.…”
Section: Introductionmentioning
confidence: 99%